Early smoke exposure is associated with asthma and lung function deficits in adolescents. (3rd July 2017) - Dai, Xin; Dharmage, Shyamali C.; Lowe, Adrian J.; Allen, Katrina J.; Thomas, Paul S.; Perret, Jennifer; Waidyatillake, Nilakshi; Matheson, Melanie C.; Svanes, Cecilie; Welsh, Liam; Abramson, Michael J.; Lodge, Caroline J.
ABSTRACT: Objective : Early life tobacco smoke exposure may influence asthma, lung function and lung function growth into adolescence. We aimed to determine the associations between perinatal smoke exposure and asthma and lung function up to 18 years of age. Methods : We prospectively recorded perinatal parental smoking and measured respiratory outcomes at 12 and 18 years in the Melbourne Atopy Cohort Study (MACS), a longitudinal birth cohort. Multiple logistic regression was used to analyse the associations between perinatal smoke exposure and asthma at 12 ( n = 370) and 18 years ( n = 411). Multiple linear regression was used to investigate the relationship between perinatal smoking and: lung function (12 and 18 years) and lung function growth (between 12 and 18 years). Results : At 18 years, girls exposed to parental smoking during the perinatal period had increased odds of asthma (OR: 3.45, 95%CI: 1.36, 8.77), reduced pre-bronchodilator Forced expiratory volume in one-second (FEV1 ) (−272 ml/s; −438, −107); FEV1 / forced vital capacity (FVC) (−0.038; −0.065, −0.010); mid expiratory flow (MEF25-75 ) (−430 ml/s; −798, −61), and reduced post-bronchodilator FEV1 /FVC (−0.028, −0.053, −0.004). No associations were found for boys (pre-bronchodilator FEV1 26ml/s; −202, 255; FEV1 /FVC 0.018; −0.013, 0.049). Conclusions : Perinatal smoke may affect risk of asthma, reduce lung function and lung function growth in adolescence. Girls appear to be more susceptible than boys.